(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
General practice nurses are professionals who play an important role in the health care system. They work directly with patients and play an important role in maintaining and improving their health. The tasks and responsibilities of a general practice nurse are wide-ranging, each of which is aimed at ensuring the health of patients.